UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMFASILITASI DAN MENDISIPLINKAN BELAJAR PESERTA DIDIK DI MASA PANDEMI COVID-19 DI MADRASAH ALIYAH BUSTANUL ULUM MIDAI, NATUNA - Nova Elda; Khoirul Asfiyak; Ika Anggraheni (VICRATINA, 2021)
This research is motivated by a phenomenon of student learning facilities and student learning discipline. Teachers facilitate student learning by meeting good facilities and infrastructure to support the ongoing teaching and learning process in school. In this study the author uses the type of field research. The method used in collecting this data is to use the method of interview, observation, and documentation. Teachers are obligd to facilitate and discipline student learning is to find out and describe the condition of the faciities and student learning discipline at MA Bustanul Ulum Midai. The results of the study indicate that the teacher’s efforts in facilitating and disciplining student learning by repairing damaged facilities, providing comfortable classes for learning, and continuing to give assignments when online school takes place. So that it can provide a little good support for the continuity of the learning process of students. Discipline students by emphasizing on student through student discipline habituation activities such as a culture of caring for the environment, coming to school on time, getting used to good manners, so that it can form spiritual knowledge for student to be used as provisions later when they are in the community. So that the main goal is to form graduates who have good moral character.